Research and Development of a High-Temperature-Resistant, Gel-Breaking Chemical Gel Plugging Agent and Evaluation of Its Physicochemical Properties - Junwei Fang; Jinsheng Sun; Xingen Feng; Lijuan Pan; Yingrui Bai; Jingbin Yang (Gels)
Gas channeling phenomena in carbonate fracture-vuggy reservoirs frequently occur, primarily in the form of negative pressure gas channeling and displacement gas channeling, with the possibility of mutual conversion between the two. This is accompanied by the risk of hydrogen sulfide (H2S) release from the reservoir, which poses significant challenges to controlling safety. Currently, liquid bridging and gel plugging technologies are effective methods for mitigating complex issues such as downhole overflow, fluid loss, and heavy oil backflow. This paper focuses on the development and optimization of key treatment agents, including high-temperature-resistant polymers and crosslinking agents, to formulate a high-temperature chemical gel plugging agent. A gel-breaking, high-strength colloidal chemical gel plugging agent system capable of withstanding temperatures up to 150 °C was developed, and it has an apparent viscosity of about 7500 mPa·s, an energy storage modulus and a loss modulus of 51 Pa and 6 Pa, respectively, after gel formation at elevated temperatures, and an apparent viscosity retention rate of the gel of greater than 82% after aging for 9 d at a temperature of 150 °C. This system forms a stable gas isolation barrier in the wellbore, with performance remaining stable after 7 to 12 days of aging, and the degradation rate reaches 99.8% after 24 h at 150 °C. This technology is of significant importance in solving complex issues such as overflow, fluid loss, and heavy oil backflow in gas injection and recovery wells in high-temperature, high-pressure reservoir conditions.